Laparoscopic approach of low-grade appendiceal mucinous neoplasm (Revista Argentina de Cirugía, 2026)
Appendiceal mucinous neoplasms are rare and are classified in low-grade mucinous neoplasm, high-grade mucinous neoplasm and mucinous adenocarcinoma. They are considered precursors of pseudomyxoma peritonei, characterized by the accumulation of mucin within the abdominal cavity. We report three cases of low-grade appendiceal mucinous neoplasm, two men and one woman, who presented with acute abdominal pain. The diagnoses were made preoperatively by computed tomography scan and the tumors were managed through laparoscopic approach (appendectomy, partial resection of the cecum and right colectomy, respectively). The three patients evolved with favorable postoperative outcome without complications. Appendiceal mucinous neoplasms are rare without specific clinical presentation. The laparoscopic approach is a safe and feasible option. The frequency and duration of surveillance in these patients are still controversial.
Keywords: appendiceal mucinous neoplasm; laparoscopic approach; appendectomy; colectomy